Espectroscopia Raman da glândula prostática: avaliação de potenciais marcadores moleculares para o câncer de próstata - Felipe Lima Magalhaes (2016)
According to National Cancer Institute of Brazil, prostate cancer is the second most common among men, and has 61.200 estimated new cases for 2016 (22.8% of total cancers diagnosed in males). Numerous classification systems have been proposed for prostate cancer. The Gleason system is the most used and recommended by the World Health Organization. In radical prostatectomy specimens, it is one of the most important prognostic factors for postoperative evaluation. Changes in this classification are still needed in order to properly correlate the Gleason score and the patient's prognosis. Raman spectroscopy is a molecular spectroscopy widely used to investigate the structure and property of the molecules from their vibrational transitions. Raman spectroscopy may allow the diagnosis of prostate cancer because of it is a non-destructive manner, rapid and objective. Thus, allowing the determination of a molecular signature that can be scaled from micrometric level in regions of interest to the macroscopic analysis regions of the analyzed tissue. This experimental study aimed to evaluate the diagnostic discrimination capability of Raman spectroscopy using the 1064nm wavelength and FT-Raman system in prostate samples having as reference the histopathological evaluation as the gold standard. Multiple prostatic samples from 8 patients who underwent radical prostatectomy were evaluated. This study showed that the technique can evaluate the scattering from different molecular compounds present in prostatic tissue, however its discriminatory capacity to distinguish between prostate glandular tissue diagnosed by pathologists as benign and glandular tissue diagnosed as cancer is unsatisfactory in both univariate and multivariate analysis. This is the first study in the literature that investigated the use of this excitatory wavelength in prostatic tissues.